The PCH family protein, Cdc15p, recruits two F-actin nucleation pathways to coordinate cytokinetic actin ring formation in Schizosaccharomyces pombe - Carnahan, Robert H. (The Rockefeller University Press, 2003)

(untitled)
Cytokinetic actin ring (CAR) formation in Schizosaccharomyces pombe requires two independent actin nucleation pathways, one dependent on the Arp2/3 complex and another involving the formin Cdc12p. Here we investigate the role of the S. pombe Cdc15 homology family protein, Cdc15p, in CAR assembly and find that it interacts with proteins from both of these nucleation pathways. Cdc15p binds directly to the Arp2/3 complex activator Myo1p, which likely explains why actin patches and the Arp2/3 complex fail to be medially recruited during mitosis in cdc15 mutants. Cdc15p also binds directly to Cdc12p. Cdc15p and Cdc12p not only display mutual dependence for CAR localization, but also exist together in a ring-nucleating structure before CAR formation. The disruption of these interactions in cdc15 null cells is likely to be the reason for their complete lack of CARs. We propose a model in which Cdc15p plays a critical role in recruiting and coordinating the pathways essential for the assembly of medially located F-actin filaments and construction of the CAR.